Production of Fuel Ethanol from Molasses by Thermotolerant Yeast (University of Khartoum Journal of Agricultural Sciences, 2025)
A thermotolerant strain of the yeast Kluyveromyces marxianus,isolated from Kenana sugar factory in the Sudan, was used for theproduction of ethanol from molasses. Fermentations were carried out in abioreactor with 10-litre working volume at three temperatures and threesugar concentrations in batch and at one temperature and three feedingrates in fed-batch processes. In the batch fermentations, the best resultswere obtained at 40°C and 20% sugar, where a maximum of 9.2% (w/v)ethanol concentration was produced in 30 hours with a yield of 90% ofthe theoretical and a maximum ethanol specific productivity of 0.65 g pergramme yeast and hour. In the fed-batch process at 40°C, the best resultswere obtained at 0.5 l/h feeding rate of a substrate with 400 g/l sugar.Under such conditions, the yeast produced up to 9.34% (w/v) ethanol with91.6% of the theoretical yield in 14 hours of fermentation and a maximumspecific ethanol productivity of 0.9 g per gramme yeast and hour.